Contribution of the Motorcycle Taxi Profession to the Reduction of the Unemployment Rate and the Impact of this Profession on the Health of Riders in Tône Prefecture (Northern Togo) - KOMBIENI, AZOUMA HERVÉ; LARE, Babenoum; NIKIEMA, Edwige (My University, 2022)
The high rate of unemployment remains one of the major problems of sub-Saharan countries. According to the National Institute of Statistics and Economic and Demographic Studies (INSEED), the rate of unemployment in Togo was 28.6% in 2013 [1]. For that reason, young Togolese have undertaken the profession of motorcycle taxis to overcome unemployment’s hardships. In the prefecture of Tône, young people are not spared. The objective of this article is to analyze the contribution of the motorcycle taxi rider's profession to the reduction of unemployment and its impact on the health of these riders. Using a mixed methodology approach (quantitative and qualitative), this study sampled 245 young people. Interviews were conducted with leaders of motorcycle taxi riders’ unions and medical staff. The data collected is processed with the Cspro 7.4 software and maps made with the Arc GIS 3.2 software. The results show that 74.8% of young people engage in this profession in the area surveyed. More than 25% suffer from diseases such as respiratory infections, cardiovascular diseases, cancer, eye disease, discharge from the nose and nervousness. This profession remains a panacea in youth entrepreneurship.
Keywords: motorcycle; taxi; rider’s health; youth unemployment; entrepreneurship; Tône prefecture.